Open economy macroeconomics in developing countries - Végh Gramont, Carlos A. (Cambridge,MA Massachusetts Institute of Technology (MIT), 2013)
This book develops a basic small open economy model and shows how it can be extended to answer many important macroeconomic questions that arise in emerging markets and developing economies, particularly those regarding monetary, fiscal, and exchange rate issues.
Includes bibliographical references and index.
lje 24/10/17
Loans
Keywords: Macroeconomic policy; Fiscal policy; Monetary policy; Developin countries